Analysis and modeling magnetic energy harvester with field shaping capacitors - Ma, Yan; Liu, Ming; Chen, Guanhong; Sun, Min; Zhang, Man; Li, Jian (Frontiers in Energy Research, 2023)
A detailed circuit model is discussed in this paper for the operation of magnetic energy harvesters with field shaping capacitors (FSC) feeding constant voltage load. First an equivalent circuit with nonlinear inductance, current source and a diode bridge was given based on the physical analysis of the harvester. Then detailed analysis of the circuit operation and state transitions under various FSC are provided. A mathematical model is established to replace the circuit model so that the optimization of the system parameters, such as number of turns, load voltage, could be carried out directly. Simulation and experimental results are given in the paper to prove the effectiveness of the proposed circuit analysis method.